INTERPROFESSIONAL COLLABORATION FOR PATIENT SATISFACTION IN INDONESIA - Al-Ghani, Muhammad Kemal Pasha; Sundari, Sri (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: One of the ways to improve healthcare quality in hospitals is patient-centered care (PCC). In improving patient-centered care, health workers can optimize interprofessional collaboration (IPC), but it remains challenging to understand how they communicate and coordinate, and thus, the impact of IPC on patient satisfaction remains unclear.    Aims: It aimed to investigate the impact of IPC implementation on patient satisfaction within the PCC in a teaching hospital. Methods: A mixed-methods design was employed in this study, comprising 140 samples, consisting of 70 healthcare providers (IPC measured by AITCS-II) and 70 patients (satisfaction assessed using a modified SERVQUAL) for the quantitative component.   Chi-square and multivariate logistic regression were used to analyze the data. The respondents, three healthcare professionals and three patients, were then interviewed to share their experiences with IPC and patients’ satisfaction. The data were then analyzed by using grounded theory (open, axial, and selective coding). Results: Interprofessional collaboration was reported to improve patient satisfaction (p = 0.016). The indicators that significantly increased the patients' satisfaction are partnership, cooperation, and coordination, with adjusted odds ratios (aORs) of 2.05, 1.80, and 1.72, respectively. These results, then, are in line with the qualitative findings, which reported that the barriers to implementing IPC include communication, teamwork, and hierarchy. Conclusion: It can be concluded that IPC can affect patient satisfaction in PCC implementation Keywords: Health Services Administration, Interprofessional Relations, Patient-Centered Care, Patient Satisfaction, Teaching Hospitals